Earlier Resolution of Symptoms and Return of Function After Bridge-Enhanced Anterior Cruciate Ligament Repair As Compared With Anterior Cruciate Ligament Reconstruction. Issue 11 (9th November 2021) - Barnett, Samuel C.; Murray, Martha M.; Badger, Gary J.; Sanborn, Ryan; Kiapour, Ata; Proffen, Benedikt; Sant, Nicholas; Fleming, Braden C.; Micheli, Lyle J.; Yen, Yi-Meng; Kramer, Dennis E.
Background: Bridge-enhanced anterior cruciate ligament repair (BEAR) has noninferior patient-reported outcomes when compared with autograft anterior cruciate ligament reconstruction (ACLR) at 2 years. However, the comparison of BEAR and autograft ACLR at earlier time points—including important outcomes such as resolution of knee pain and symptoms, recovery of strength, and return to sport—has not yet been reported. Hypothesis: It was hypothesized that the BEAR group would have higher outcomes on the International Knee Documentation Committee and Knee injury and Osteoarthritis Outcome Score, as well as improved muscle strength, in the early postoperative period. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: A total of 100 patients aged 13 to 35 years with complete midsubstance anterior cruciate ligament injuries were randomized to receive a suture repair augmented with an extracellular matrix implant (n = 65) or an autograft ACLR (n = 35). Outcomes were assessed at time points up to 2 years postoperatively. Mixed-model repeated-measures analyses were used to compare BEAR and ACLR outcomes. Patients were unblinded after their 2-year visit. Results: Repeated-measures testing revealed a significant effect of group on the International Knee Documentation Committee Subjective Score ( P = .015), most pronounced at 6 months after surgery (BEAR = 86 points vs ACLR = 78 points; P = .001). There was a significant effect of group on the Knee injury and Osteoarthritis Outcome Score-Symptoms subscale scores ( P = .010), largely attributed to the higher BEAR scores at the 1-year postoperative time point (88 vs 82; P = .009). The effect of group on hamstring strength was significant in the repeated-measures analysis ( P < .001), as well as at all postoperative time points ( P < .001 for all comparisons). At 1 year after surgery, approximately 88% of the patients in the BEAR group and 76% of the ACLR group had been cleared for return to sport ( P = .261). Conclusion: Patients undergoing the BEAR procedure had earlier resolution of symptoms and increased satisfaction about their knee function, as well as improved resolution of hamstring muscle strength throughout the 2-year follow-up period. Registration: NCT02664545 (ClinicalTrials.gov identifier)